Dynamical behaviors of an epidemic model for malware propagation in wireless sensor networks - Zhou, Ying; Wang, Yan; Zhou, Kai; Shen, Shou-Feng; Ma, Wen-Xiu (Frontiers in Physics, 2023)
To study the influence of malware on wireless sensor networks (WSNs), we propose a Susceptible-Unexposed-Infected-Isolation-Removed epidemic model to describe the malware spreading. First, we establish a nonlinear dynamic equation of malware propagation. Then, the basic reproductive number is derived by using the next-generation method. Finally, we carry out numerical simulations to observe the malware spreading in WSNs to verify the obtained theoretical results. Furthermore, we investigate the communication range of the nodes to make the results more complete. The optimal range of nodes is designed to control the malware propagation.